Dynamic Analysis of Point Contact Gears with Circular-parabola Configuration Based on Adams Software - Liang Dong; Jiang Peng; Li Ming; Xu Xiangyang; He Zeyin (Jixie chuandong)
Taking the point contact gear with circular-parabola configuration as the research object, based on the Adams dynamic analysis software, dynamic characteristics and the variable law of tooth surfaces are studied in this study. Firstly, according to space meshing theory, tooth surfaces equation of the point contact gear with circular-parabola configuration is derived, and three-dimensional solid models of gear pairs are established by the given design parameters. Secondly, the virtual prototype of point contact gears with circular-parabola configuration is established utilizing Adams software. Through simulation process, variation law of normal contact force, circumferential force, radial force and axial force of the gear are discussed. Change law of normal contact force under the same parameters and working conditions are analyzed between the point contact gear with circular-parabola configuration and general involute helical gears. Influences of meshing stiffness on normal contact force of the gear are also discussed. Research results show that the dynamic performance of point contact gears with circular-parabola configuration is better than that of general involute helical gears under the same parameters and working conditions. Meshing stiffness has a certain influence on the dynamic performance of tooth surfaces. For a reasonable variable range, the transmission process will be more stable with the increase of the meshing stiffness. The study can provide a basis for the design of point contact gears with circular-parabola configuration.